Pengenalan Bahasa dan Budaya Indonesia pada Anak-anak Pekerja Migran Indonesia di SB AMI Penang Malaysia - Yulia Mutmainnah (Ambacang: Jurnal Inovasi Pengabdian Masyarakat, 2026)
The large number of Indonesian Migrant Workers (PMI) in Malaysia, including undocumented workers, has limited their children’s access to formal education and contributed to cultural identity issues. This community service program aimed to enhance Indonesian language literacy and strengthen national identity through folklore and traditional games. Implemented participatively at Sanggar Belajar AMI Penang, Malaysia, the program included socialization, interactive training, digital media utilization, and mentoring with evaluation. Activities involved storytelling of Candi Prambanan and Malin Kundang, cultural videos, and the traditional game cublak-cublak suweng. Results indicate improved engagement, language skills, and cultural pride among participants. The program demonstrates the effectiveness of culturally based literacy initiatives for Indonesian migrant communities abroad.